2022
DOI: 10.3389/fmolb.2022.1077968
|View full text |Cite
|
Sign up to set email alerts
|

A review on the role of miR-671 in human disorders

Abstract: miR-671 is encoded by a gene on 7q36.1 and contributes to the pathogenesis of a variety of disorders, including diverse types of cancers, atherosclerosis, ischemic stroke, liver fibrosis, osteoarthritis, Parkinson’s disease, rheumatoid arthritis, acute myocardial infarction and Crohn’s disease. In the context of cancer, different studies have revealed opposite roles for this miRNA. In brief, it has been shown to be down-regulated in pancreatic ductal carcinoma, ovarian cancer, gastric cancer, osteosarcoma, eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 99 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…In the present study, miR-671-5p was predicted to interact with SATB2-AS1. miR-671-5p which is encoded by the gene located in 7q36.1, is frequently amplified in GBM, and promotes proliferation and metastasis of GBM cells ( 24 , 35 ). As for the oncogenic role of miR-671-5p in glioma, there are other 2 related studies; for instance, circ_0001946 was found to inhibit GBM progression by sponging miR-671-5p ( 36 ) and circDLC1 was revealed to suppress the malignant proliferation of glioma by competitively binding to miR-671-5p ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-671-5p was predicted to interact with SATB2-AS1. miR-671-5p which is encoded by the gene located in 7q36.1, is frequently amplified in GBM, and promotes proliferation and metastasis of GBM cells ( 24 , 35 ). As for the oncogenic role of miR-671-5p in glioma, there are other 2 related studies; for instance, circ_0001946 was found to inhibit GBM progression by sponging miR-671-5p ( 36 ) and circDLC1 was revealed to suppress the malignant proliferation of glioma by competitively binding to miR-671-5p ( 37 ).…”
Section: Discussionmentioning
confidence: 99%